Protection and preservation of the marine environment through human rights-based approach: potentials, limitations and recommendations - Di, Lei; Yin, Bowen (Frontiers in Marine Science, 2025)
The deterioration and degradation of the marine environment is having an increasingly obvious and serious impact on human rights. This article introduces a human rights-based approach to the issue of protecting and preserving the marine environment. The extraterritorial application of human rights treaties at sea and the open-ended nature of the United Nations Convention on the Law of the Sea enable the human rights-based approach to be effectively integrated with marine issues. Although this human rights-based approach can add a humanitarian dimension to marine environmental governance, facilitate the interpretation of relevant provisions, and enhance the legitimacy of certain environmental enforcement measures of coastal states, the direct approach relying on environmental rights lacks sufficient normative basis, and the indirect approach relying on other affected human rights cannot effectively address marine environmental issues per se. This article suggests a comprehensive human rights orientation that balances collective rights with individual rights, civil and political rights with economic, social, and cultural rights in the process of safeguarding the rights of indigenous groups and the right to public participation. Incorporating good practices from regional and national levels, this approach can advance the international lawmaking process for establishing a human right to a clean, healthy and sustainable marine environment.